GOLEK AYUN-AYUN DANCE AS A REALIZATION OF JAVA PHILOSOPHY IN HERMENEUTIC PERSPECTIVE - Kaizuka, Risa (Imaji: Jurnal Seni dan Pendidikan Seni, 2021)
This article aims to see the Golek Ayun-Ayun dance as a manifestation of Javanese philosophy from a hermeneutic perspective. The way of writing is by interpreting the Golek Ayun-Ayun dance performance elements, starting from elements of dance movements to elements of clothing. The results of this writing indicate that the Golek Ayun-Ayun dance is a dance that is not staged for entertainment only, but this dance has a Javanese philosophical meaning from movement, clothing, to decoration. The manifestations are: (1). The Sembahan movement (forward beksan) with the position of joining the hands and thumbs affixed in front of the chest is a symbol of greeting horns to God, the Sultan, and the guests so that the attitude of this dance is to maintain good manners, tolerance, and respect for others. (2). The batik cloth of the parang rusak with the gurdha machete motif is a symbol of adoration. (3). The Jamang Elar decoration is a headband given a variety of menthog feathers as a symbol of a girl in bloom. Golek Ayun-Ayun dance has excellent characteristics (high quality) and many layers of meaning. Keywords: Golek Ayun-Ayun dance, meaning, Javanese philosophy